The Effect of Surface Water On The Slope Of “X” Housing Gunung Geulis, Cimanggung District, Sumedang Regency - Putri, Revena Denia; Sophian, Raden Irvan; Zakaria, Zufialdi; Khoirullah, Nur (Journal of Geological Sciences and Applied Geology, 2021)
Rainfall intensity can affect water infiltration to the ground. The increase in groundwater level will increase pore pressure (μ) that minimizes shear resistance of the slope mass, especially on the ground material (soil). The increase in surface water levels also increases surface water discharge and increases erosion below the surface (piping or subaqueous erosion). As a result of more subtle friction (silt) from the time that washed away soil, the soil will decrease future resilience. This happened in Subdistrict Cimanggung, Sumedang, West Java. This area is composed of weathered soil of volcanic products such as tuff, volcanic breccia, and andesitic lava. The parameters of this research contain basic properties and mechanical properties of soil, slope profile in MH soil, and water surface level. This research aims to determine basic properties and mechanical properties of soil, as well as the effects of groundwater level, that can give recommendations for groundwater level to get a stable condition of the slope. The basic properties and mechanical properties of soil are known based on laboratory tests from a disturbed and undisturbed soil sample were obtained by surface sampling and geotechnical hand drilling. Slopes were analyzed by the Bishop method using Rockscience Slide software. The result is there’s an increase in the value of safety factors when the level of surface water level decrease. From the value of the safety factor that varies between slope sections, that slope can be stable if water surface level -7,5 meters beneath the surface.